A low cost synthesis method for functionalised iron oxide nanoparticles for magnetic hyperthermia from readily available materials. (30th September 2014) - Bear, Joseph C.; Yu, Bin; Blanco-Andujar, Cristina; McNaughter, Paul D.; Southern, Paul; Mafina, Marc-Krystelle; Pankhurst, Quentin A.; Parkin, Ivan P.
Abstract : The synthesis of iron oxide nanocrystals from reagents taken from high street sources using thermal decomposition of an iron–fatty acid precursor in a high boiling point solvent in the presence of surfactants is presented. The nanocrystals were characterised using a variety of techniques including: electron microscopy, X-ray dispersive spectroscopy, infrared spectroscopy, X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and magnetometry. Thermogravimetric analysis (TGA) is also used to compare the decomposition behaviour of iron oleate and iron palmitate, our nanoparticle precursors. The nanoparticles also exhibit shape anisotropy when prepared under optimum conditions. We show that these nanoparticles have potential in magnetic hyperthermia after transfer to aqueous media via an amphiphilic polymer.